2017
DOI: 10.3748/wjg.v23.i17.3077
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy in patients ≥ 75 years of age: Are there any differences with other age ranges in oncological and surgical outcomes? Results from a tertiary referral center

Abstract: AIMTo compare surgical and oncological outcomes after pancreaticoduodenectomy (PD) in patients ≥ 75 years of age with two younger cohorts of patients.METHODSThe prospectively maintained Institutional database of pancreatic resection was queried for patients aged ≥ 75 years (late elderly, LE) submitted to PD for any disease from January 2010 to June 2015. We compared clinical, demographic and pathological features and survival outcomes of LE patients with 2 exact matched cohorts of younger patients [≥ 40 to 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
0
27
2
Order By: Relevance
“…Data regarding oncological outcomes after pancreatic surgery for malignancies in the elderly are controversial so far. Some authors report that the elderly population shows a worse outcome [5,17]; however, other groups did not find any significant survival difference [4,9,28]. This heterogeneity of results is probably due to selection biases, but our sample also shows a comparable overall survival between older and younger groups.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Data regarding oncological outcomes after pancreatic surgery for malignancies in the elderly are controversial so far. Some authors report that the elderly population shows a worse outcome [5,17]; however, other groups did not find any significant survival difference [4,9,28]. This heterogeneity of results is probably due to selection biases, but our sample also shows a comparable overall survival between older and younger groups.…”
Section: Discussioncontrasting
confidence: 54%
“…In this study, the "frailty" of elderly patients is confirmed by a significantly higher rate of ASA Score 3 and a poorer performance status compared to younger patients (Table 1); however, intraoperative data did not show significant differences in terms of operative time, blood loss, lymph node retrieval, and radicality of resection, demonstrating that surgical technique and extent of resection is not affected by age of patients [9]. Considering postoperative mortality (90-day mortality), our data suggest a trend towards a worse outcome in the elderly group even though this is without statistical significance; a lack of significance could be related to sample size, but it is important to consider that in-hospital deceases, directly related to surgical operation, were similar (1 in group I and 1 in group II), while the other 2 deaths among older patients occurred from heart failure after discharge.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…That older age is negatively associated with OS in this analysis may in part, be related to additional comorbidities and shorter overall life expectancy in this age group as well as the extent of surgery required. Although some series have reported higher rates of surgical morbidity in elderly patients undergoing pancreatoduodenectomy, these reports have generally referred to octogenarian or more elderly patients . We submit that treatment for AAC not be based on any specific age, but rather an overall assessment of the individual patients' performance status, social support, and personal decisions based on appropriate information and education regarding the risks and benefits of therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Although some series have reported higher rates of surgical morbidity in elderly patients undergoing pancreatoduodenectomy, these reports have generally referred to octogenarian or more elderly patients. [11][12][13][14][15] We submit that treatment for AAC not be based on any specific age, but rather an overall assessment of the individual patients' performance status, social support, and personal decisions based on appropriate information and education regarding the risks and benefits of therapy. and potentially under treatment for these patients.…”
Section: Survival Analysismentioning
confidence: 99%